(untitled) (Research, Society and Development, 2020)
With the intention of carrying out a study that addressed the integration of students’ knowledge, with in the perspective of vertical education, in this case the union of students from technical high school to postgraduate, building the so-called vertical education, the Genetikar Workshop was created. A Project with specific contents of theTechnical High School in Environmental Control, aimed to discuss scientific concepts of genetics for its approach toth estudents’ daily life. The workshop hás been structured on the following question: “How can the interaction between Genetic, Science and Art knowledge, and laboratory practices, based on TAS, facilitate the learning of scientific content for students of technical education?” This workshop was built through of Meaningful Learning Theory (MLT) methodology and took place in two consecutive years. As results we sought to focus on two essential products that can answer the question proposed in the workshop, they are: the didactic sequential organization of the workshop, and the works produced by the students attheend of it. Thus, it is possible to perceive through the dialogue and works presented during the workshop, the integration of the proposed knowledge; concluding that, through the analyzed material and the construction of its own sequential organization, there were signs of a Meaningful Learning of scientific concepts seen in the workshop.